Real-time colorimetric hydration sensor for sport activities - Zhou, Yubin (2017)
Dehydration and over-hydration are a serious health concern in endurance sport activities, especially in tropical climates. Current methods for detection are inconvenient and not widely applied. Point-of-care hydration monitoring during a sport event is an ideal preventative therapy, as it allows personalize real-time feedback towards preventing hydration related injuries.Gold nanoparticles allow colorimetric detection, whose color changes due to changes in colloidal stability. The red-shift in the plasmonic band induces a color change from red to purple upon aggregation that can be observed by the naked eye, which gives promising applications in point-of-care preventative therapies. We developed a gold nanoparticle-based colorimetric sensor for rapid detection of dehydration and over-hydration by monitoring ‘proof-of-concept’ artificial sweat ion concentrations. The colorimetric sensor was designed to distinguish between dehydration and over-hydration through easily observed color changes. In addition, the sensor exhibited a fast response time within minutes. The designed sensor is a promising tool for point-of-care and real-time detection of dehydration and over-hydration.